RANCANG BANGUN WEBSITE SEKOLAH PADA SMP NEGERI 05 SIPIROK - Tivani Yona Silvia, (2022)
Websites are needed in a school to meet the internal and external needs of the school. With the website, it can make it easier for schools to provide information related to schools to the community. How to design and create a website for SMP Negeri 05 that is able to provide convenience for schools and the community in providing and receiving school-related information quickly, accurately and efficiently. It is hoped that the creation of this school website can make it easier for schools to deliver information about schools to outsiders, can make it easier for parties outside the school who want to know information about SMP Negeri 05 Sipirok. which can facilitate the delivery of school-related information to parties outside the school. With the construction of this website is expected to facilitate the school in managing the information provided to the public. The website created can help the school to be able to introduce / promote the school in a more efficient way. With the school website, it will provide convenience for the school in managing the information to be submitted.